The Dependence of Cotton Yield on Plant Density When Grown Under Film - Bakhodirbekovna, Mamadalieva Saida (American Journal of Botany and Bioengineering, 2026)
In the second period from March 15 to 25, the seeds of cotton variety UzPITI-201 when sown under transparent film with a plant density of an average of 95.5 and 155.4 thousand plants / ha and at mineral fertilizer rates of N 180 P 125 K 90 kg / ha with optimal irrigation of 70-75-60% compared to HB compared to the control options (8-9-10 options) sowing seeds in the usual open way with two-row and single-row planting were provided with nutrients at a higher level and had the property of longer retention of soil moisture and due to favorable soil conditions under transparent film, an additional yield of 7.2 and 9.3 c / ha was obtained.